Evaluation of Lepto Dri Dot as a rapid test for the diagnosis of leptospirosis. - Vijayachari, P. (Cambridge University Press, 2002)
Lepto Dri Dot is a new card agglutination test developed by the Dutch Royal Tropical Institute for the rapid diagnosis of leptospirosis. We evaluated the test in field conditions in The Andaman Islands. Patients suspected of leptospirosis who attended three primary health centres were included in the study. The test results were compared with blood culture or microscopic agglutination tests on paired serum samples; 74 of 124 patients were diagnosed as having leptospirosis based on these criteria. Lepto Dri Dot had a sensitivity of 67.6% (50/74) and a specificity of 66.0% (33/50) during week 1. During weeks 2-4 the values increased to 85.5% (47/55) and 80% (40/50) respectively. An IgM ELISA was also performed on the serum samples for comparison and this was marginally less sensitive, but more specific, during the first week of illness. The positivity rates for the Dri Dot test during days 2-3, 4-5 and 6-7 were 53.1% (17/32), 75.0% (18/24) and 83.3% (15/18), respectively. The corresponding values for ELISA were 28.1% (9/32), 54% (13/24) and 77.8% (14/18). Both Dri Dot and ELISA showed good agreement with the standard diagnostic criteria after the first week of illness (kappa= 0.65 and 0.74, respectively). The overall concordance of the two tests was 89.5 % (kappa = 0.79). The test does not require special storage or sophisticated equipment and can be performed by relatively low skilled personnel.